Catalyst system for olefin polymerization

CN122996092APending Publication Date: 2026-10-27SABIC GLOBAL TECHNOLOGIES BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580023745.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2025-02-28
Publication Date
2026-10-27

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention relates to a dual metal catalyst system for the polymerization of olefins comprising a first catalyst component A and a second catalyst component B, wherein each of A and B is a bridged metallocene catalyst compound, wherein one of A and B comprises a 1,2-phenylene bridge and wherein the other of A and B comprises a 2,2'-biphenyl bridge. Such catalyst systems allow for the copolymerization of ethylene with reverse comonomer incorporation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to catalyst systems for olefin polymerization. Background Technology

[0002] Currently, the methods used for olefin polymerization account for the majority of global polymer material production methods. These methods can produce a wide range of polyolefin materials, making the resulting polymers suitable for various applications.

[0003] To produce desired polyolefin materials, various types of polymerization methods have been developed, each targeting the production of polymers with specific molecular structures, based on a specific formulation of the monomer materials to be used as reactants. These polymerization methods can operate with a single type of monomer material to produce homopolymers, or use combinations of multiple monomer materials to produce copolymers.

[0004] A significant portion of olefin polymerization methods involve the use of catalysts to accelerate the polymerization reaction. Over the past seventy years, numerous catalyst systems have been developed, most notably Ziegler-Natta, chromium-based, and monoparticle-based systems, with metallocene catalysts being particularly well-known. Extensive work continues to develop these catalyst systems further to improve polymerization methods and the properties of the produced polymers.

[0005] The most mature polyolefin materials are ethylene-based polymers and propylene-based polymers. Catalytic methods for producing these polymers can be carried out in gas-phase reactions, slurry reactions, or solution reactions. Continuous development of catalyst systems continues to lead to improvements in the production methods and material properties of polyolefin materials. There remains a persistent expectation for further development of catalyst systems to obtain more advantageous methods and polyolefin materials.

[0006] A particularly relevant class of polyolefin materials are ethylene-based copolymers. These copolymers are produced by reacting ethylene with one or more other olefin comonomers, particularly with monoolefinic linear α-olefins. Typical comonomers used include 1-butene, 1-hexene, and 1-octene. Typically, ethylene is present as the major reactant by weight, and the comonomers are present as minor components.

[0007] In such copolymers, ethylene molecules and comonomer molecules react to form polymer molecules, wherein ethylene-based and comonomer-based structural portions are distributed along the polymer chain in a specific manner. The comonomer-based structural portions form certain branches of the polymer chain, originating from the tailing of molecules into the α-olefin unsaturated bonds of the polymer chain during the reaction. This branching of the polymer chain caused by comonomer incorporation is called short-chain branching, also known as SCB in this paper.

[0008] The incorporation distribution of SCBs in ethylene-based copolymers can vary and is influenced by polymerization conditions and the choice of catalyst system. Furthermore, in catalytic ethylene polymerization, the polymer chain lengths follow a certain distribution; compared to the average polymer chain length, some chains may be longer than others.

[0009] It is possible for higher concentrations of SCB to occur in shorter chains or longer chains compared to the average. Short-chain branching in ethylene-based polymers is typically expressed as the number of SCBs per 1,000 (one thousand) carbon atoms in the polymer chain.

[0010] A particular architecture of ethylene-based polymer molecules is characterized by a higher concentration of SCBs (saturated comonomers) in the longer chain portions of the polymer composition compared to the shorter chain portions. This architecture is known as reverse comonomer incorporation; relatively lower incorporation in the shorter chain and relatively higher incorporation in the longer chain. Polymers with this architecture can be referred to as reverse CCD polymers; where CCD should be understood as the chemical composition distribution.

[0011] Such inverse CCD-based ethylene polymers may possess certain desirable properties, including a good balance between rigidity and toughness. Without being bound by any theory, it is thought that when ethylene-based polymers have an inverse CCD, the lower molecular weight fraction (i.e., the fraction with shorter chains) exhibits higher crystallinity, which can be attributed to improved rigidity. The presence of a greater amount of SCB in the longer chains is considered to be attributable to higher toughness, as the presence of more chain branches is thought to allow for more intermolecular connections or entanglements.

[0012] Therefore, it is desirable to obtain such a reverse CCD based on an ethylene polymer material. Summary of the Invention

[0013] For example, this polymer can be produced using cascade reactor technology or via a specially designed catalyst system. A suitable catalyst system that allows for the incorporation of appropriate reverse CCD comonomers in a single polymerization reactor is particularly desirable, as this clearly benefits process economics. There is a persistent need to develop such a catalyst system, which is now addressed according to the present invention via a catalyst system comprising a first catalyst component A and a second catalyst component B.

[0014] Component A is a component according to formula (I):

[0015]

[0016] And component B is a component according to formula (II):

[0017]

[0018] Where R1 and R2 are different and are preferably selected from and ;

[0019] Each R12 is individually selected from H or an alkyl moiety containing 1-10 carbon atoms, preferably each R12 is individually selected from H, CH3 and phenyl moiety, more preferably each R12 is individually selected from H, CH3 and phenyl moiety and each R12 is the same;

[0020] R3 is a structural moiety selected from ZrX2, HfX2 and TiX2, and X is selected from the group consisting of halogen, alkyl, aryl and aralkyl.

[0021] R4-R11 are each hydrogen or a hydrocarbon structural moiety containing 1 to 20 carbon atoms, or R4 and R5, R5 and R6, R8 and R9 and / or R9 and R10 are fused to form a cyclic hydrocarbon structural moiety containing 4 to 20 carbon atoms, preferably wherein the cyclic hydrocarbon structural moiety is a structural moiety containing a cyclohexene ring or a benzene ring, which may contain substituents containing 1 to 10 carbon atoms.

[0022] The preferred bridging structure portion R1 contains at least one aryl group.

[0023] Each R3 is preferably selected from TiCl2, ZrCl2, HfCl2, Ti(CH3)2, Zr(CH3)2 and Hf(CH3)2, and more preferably from ZrCl2 and Zr(CH3)2.

[0024] In a preferred embodiment, R1 and R2 are each selected from 1,2-phenylene: and 2,2'-biphenyl: .

[0025] Component A is also preferred according to formula (III):

[0026]

[0027] R4, R7, R8 and R11 are each individually selected from H, CH3, tert-butyl or phenyl; preferably R1 is 2,2'-biphenyl.

[0028] Component A may be selected, for example, from the following components: [2,2'-bis(2-indenyl)biphenyl]zirconium chloride, [2,2'-bis(2-indenyl)biphenyl]hafnium chloride, [2,2'-bis(2-(4,7-dimethyl)indenyl)biphenyl]zirconium chloride, [2,2'-bis(2-(4,7-dimethyl)indenyl)biphenyl]hafnium chloride, [2,2'-bis(2-(4,5,6,7-tetrahydro)indenyl)biphenyl]zirconium chloride, [2,2'-bis(2-(4,5,6,7-tetrahydro)indenyl)biphenyl]hafnium chloride, [2,2'-bis(2-(5-fluoro)indenyl)biphenyl]zirconium chloride, [2,2'-bis(2-(5-fluoro)indenyl)biphenyl]hafnium chloride [2,2'-bis(2-(2-fluoro)indyl)biphenyl]zirconium dichloride, [2,2'-bis(2-(2-fluoro)indyl)biphenyl]hafnium dichloride, [2,2'-bis(2-(4,6-diisopropyl)indyl)biphenyl]zirconium dichloride, [2,2'-bis(2-(4,6-diisopropyl)indyl)biphenyl]hafnium dichloride, [2 [2,2'-bis(2-(4,6-dimethyl)indyl)biphenyl] zirconium chloride, [2,2'-bis(2-(4,6-dimethyl)indyl)biphenyl] hafnium chloride, [2,2'-bis(2-(5,6-cyclopentyl)indyl)biphenyl] zirconium chloride and [2,2'-bis(2-(5,6-cyclopentyl)indyl)biphenyl] hafnium chloride.

[0029] The preferred component A is [2,2'-bis(2-(4,5,6,7-tetrahydro)indenyl)biphenyl]zirconium dichloride (IV).

[0030] In another embodiment, component B is according to formula (IV):

[0031]

[0032] R4, R5, R6, R7 and R8 are each individually selected from H, CH3, tert-butyl or phenyl, preferably R4, R5 and R6 are each CH3, and preferably R7 and / or R8 are phenyl; preferably R2 is 1,2-phenylene.

[0033] Component B may be selected, for example, from the following components: 1,2-phenylene-[(2-methyl-1-indenyl)(1-phenyl-2-benzo[e]indenyl)]zirconium dichloride (IV), 1,2-phenylene-[(2-methyl-1-indenyl)(1-phenyl-2-benzo[e]indenyl)]hafnium dichloride (IV), 1,2-phenylene-[(1-methyl-3-phenyl-2-indenyl)(4,7-dimethyl [2,4,7-trimethyl-1-indene)(1-phenyl-2-indene)] zirconium dichloride (IV), 1,2-phenylene-[(1-methyl-3-phenyl-2-indene)(4,7-dimethyl-2-indene)] hafnium dichloride (IV), 1,2-phenylene-[(2,4,7-trimethyl-1-indene)(1-phenyl-2-indene)] zircon ... 2-Indene)] Hafnium dichloride (IV), 1,2-Phenylidene-[(3,4-dimethylcyclopentadienyl)(1,3-dimethyl-2-indene)] Zirconium dichloride (IV), 1,2-Phenylidene-[(3,4-dimethylcyclopentadienyl)(1,3-dimethyl-2-indene)] Hafnium dichloride (IV), 1,2-Phenylidene-[(3,4-diphenylcyclopentadienyl)(1,3-dimethyl- 2-Indene)]Zrconium dichloride (IV), 1,2-Phenylidene-[(3,4-diphenylcyclopentadienyl)(1,3-dimethyl-2-indene)]hafnium dichloride (IV), 1,2-Phenylidene-[(tetramethylcyclopentadienyl)(1-phenyl-2-indene)]Zrconium dichloride (IV) and 1,2-Phenylidene-[(tetramethylcyclopentadienyl)(1-phenyl-2-indene)]hafnium dichloride (IV).

[0034] Particularly preferred component B is 1,2-phenylene-[(2,4,7-trimethyl-1-indenyl)(1-phenyl-2-indenyl)]zirconium dichloride (IV).

[0035] The molar ratio of component A to component B can be, for example, 0.1-100, preferably 0.1-10, more preferably 0.1-5.0, more preferably 0.1-4.0, and even more preferably 0.2-1.5.

[0036] More preferably, component A and component B are loaded on a carrier, preferably both components are loaded on the same carrier, preferably the carrier is selected from silicon dioxide, alumina, magnesium oxide, titanium dioxide, zirconium dioxide, clay, zeolite, graphite and polymer particles, preferably silicon dioxide.

[0037] The carrier material is preferably silica, and more preferably has a density of 50-1000 μm. 2 Particles with a specific surface area of ​​0.5-3.0 g / cm³. Preferably, silica has a specific surface area of ​​0.5-3.0 g / cm³. 3The pore volume. Silica, for example, can have an average particle size of 3-20 μm. Silica with this average particle size is suitable for catalyst systems used in solution polymerization methods. Silica, for example, can have an average particle size of 30-100 μm. Silica with this average particle size is suitable for catalyst systems used in gas-phase polymerization methods. Silica, for example, can have an average particle size of 5-80 μm. Silica with this average particle size is suitable for catalyst systems used in slurry polymerization methods.

[0038] The silica is preferably dehydrated at a temperature of ≥400°C, more preferably ≥400°C and ≤700°C, and even more preferably ≥550°C and ≤700°C for a duration of ≥2 and ≤8 hours, preferably ≥4 and ≤8 hours. This dehydration is preferably carried out under a nitrogen atmosphere.

[0039] In a preferred embodiment, the catalyst system includes a co-catalyst. The co-catalyst can be an organoaluminum compound or a noncoordinate anionic compound. For example, the co-catalyst can be methylaluminoxane, perfluorophenylborane, triethylammonium tetra(pentafluorophenyl)borate, triphenylcarbium tetra(pentafluorophenyl)borate, trimethylsilyl tetra(pentafluorophenyl)borate, 1-pentafluorophenyl-1,4-dihydroborazon, tributylammonium 1,4-bis(pentafluorophenyl)borazon, or triphenylcarbium 1-methylborazon. Methylaluminoxane is a preferred co-catalyst.

[0040] In embodiments where an organoaluminum compound is used as a cocatalyst, the molar ratio of the cocatalyst to the sum of components A and B can be, for example, 1-2000, preferably 50-500.

[0041] In a specific embodiment, the catalyst system may, for example, contain ≥6.0 and ≤40.0 wt%, preferably ≥7.0 and ≤35.0 wt%, more preferably ≥10.0 and ≤30.0 wt% Al, relative to the total weight of the catalyst system.

[0042] In a specific embodiment, the catalyst system may, for example, contain ≥0.10 and ≤1.00 wt%, preferably ≥0.15 and ≤0.50 wt%, more preferably ≥0.15 and ≤0.30 wt% of the sum of Zr, Hf and Ti, relative to the total weight of the catalyst system.

[0043] The present invention also relates to methods for producing catalyst systems according to certain embodiments, wherein the method comprises the following sequential steps:

[0044] (i) Treat the support with a co-catalyst, and then

[0045] (ii) Add components A and B;

[0046] or

[0047] (i) Treat components A and B with a co-catalyst, and then

[0048] (ii) Add the carrier;

[0049] or

[0050] (i) Treat components A and B with a co-catalyst to obtain activated components A and B;

[0051] (ii) Treating the support with a co-catalyst to obtain an activated support; and

[0052] (iii) Combine the activated carrier with the activated components A and B.

[0053] The present invention also relates to a method for polymerizing a reaction mixture comprising ethylene and / or propylene using a catalyst system. Such a method may be, for example, a homopolymerization or copolymerization of ethylene or a homopolymerization or copolymerization of propylene. For example, such a polymerization method may be a copolymerization of ethylene with one or more comonomers selected from 1-butene, 1-hexene, and 1-octene. For example, such a polymerization method may be a copolymerization of propylene with one or more comonomers selected from ethylene, 1-butene, and 1-hexene. The homopolymer or copolymer of ethylene produced according to such a method may, for example, have a content of 0.860-0.970 g / cm³. 3 The density.

[0054] Such polymerization methods can be, for example, solution polymerization, gas-phase polymerization, slurry polymerization, or bulk polymerization. Such slurry polymerization methods can be carried out, for example, in an autoclave or loop reactor. Such gas-phase methods can be carried out, for example, in a fluidized bed reactor, operating, for example, in condensation or ultracondensation mode.

[0055] The invention will now be described by way of the following non-limiting embodiments.

[0056] In the context of this invention, the following materials were used in the experiments.

[0057] Table 1: Materials used.

[0058]

[0059] All materials were handled under a nitrogen atmosphere using the Schlenk technique or in a nitrogen-filled glove box. Nitrogen, isopentane, and other solvents were dried on a molecular sieve bed. The catalyst system was prepared under temperature-controlled conditions with stirring in a silicone oil bath, within ±0.5 °C of the set temperature.

[0060] MET-B Synthesis

[0061] [Description of the composition cat205]

[0062] To obtain MET-B, a synthesis involving the following first step was performed: reacting 2′,5′-dimethylphenylacetone with 2-bromobenzaldehyde to obtain 3-(2-bromophenyl)-2-methyl-1-(2,5-dimethylphenyl)-2-propen-1-one (compound A):

[0063]

[0064] Reaction of compound A with polyphosphoric acid yields 3-(2-bromophenyl)-2,4,7-trimethyl-2,3-dihydro-1H-inden-1-one (compound B):

[0065]

[0066] Reaction of compound B with NaBH4 yields 1-(2-bromophenyl)-2,4,7-trimethyl-1H-indene (compound C):

[0067]

[0068] Compound C was reacted with 4,4,5,5-tetramethyl-2-(3-phenyl-1H-inden-2-yl)-1,3,2-dioxoborane in Cs₂CO₃ and 1,4-dioxane (dioxin), followed by the addition of Pd(PPh₃)₄ to give 2,4,7-trimethyl-1-(2-(3-phenyl)-1H-inden-2-yl)phenyl)-1H-indenene (compound D):

[0069]

[0070] Compound D was reacted with n-butyllithium, Zr(NMe2)Cl2(THF)2 and MeSiCl2 in toluene to give 1,2-phenylene-[(2,4,7-trimethyl-1-indene)(1-phenyl-2-indene)]zirconium dichloride (IV), with catalyst compound MET-B.

[0071] Preparation of supported metallocene catalyst systems

[0072] Several supported metallocene catalyst systems were prepared according to the following procedure. The quantity and properties of the materials used, as well as the contents of Zr and Al in the catalyst systems, are shown in Table 2.

[0073] The support was pre-dehydrated at 600°C for 4 hours. 2.5 g of the pre-dehydrated support was placed in a 100 ml two-necked Schlenk flask under a nitrogen atmosphere in a glove box, followed by the addition of 15 ml of toluene. After shaking, a silica suspension was obtained. Activation was performed by mixing the given amounts of the metallocene catalyst compound listed in Table 2 with 12.4 ml of co-catalyst in a 25 ml vial at room temperature for 10 minutes in a glove box, also under a nitrogen atmosphere. The activated metallocene thus obtained was transferred to the silica suspension. 3.64 mg of CHA and 7.28 mg of TIBAL were mixed with 10 ml of toluene in another 25 ml vial at room temperature in a glove box, and then transferred to the suspension. The final mixture was heated to 95°C and maintained at that temperature for 5 hours. Subsequently, the product was dried under vacuum at 75°C to obtain the supported catalyst system, which was then separated into free-flowing powder. The Zr and Al contents in the catalyst system were 0.18 wt% and 14.0 wt%, respectively.

[0074] Table 2: Composition of the catalyst system

[0075]

[0076] Polymerization Experiment

[0077] A series of polymerization experiments were conducted using catalyst systems A1-A3 to determine the performance of each catalyst system in ethylene polymerization.

[0078] A 1.6L stainless steel reactor vessel equipped with a spiral stirrer and a heating / cooling control unit was heated to 110°C for 2 hours at a nitrogen flow rate of 100 g / h. Afterward, the reactor was pressurized and purged with nitrogen, followed by ethylene purging. This purging cycle was repeated three times.

[0079] The reactor was then cooled to 88°C under ethylene pressurization to 10 bar. After venting, 4 ml of SC was added via a co-catalyst injection pump. Nitrogen was introduced to maintain a nitrogen pressure of 8 bar. Then, ethylene and 1-hexene with the given molar ratio shown in Table 3 were introduced into the reactor under controlled mass flow rate parameters to maintain a pressure of 10 bar for both ethylene and 1-hexene in the reactor. After reaching stable temperature and pressure levels, 40 mg of the catalyst system was injected via a catalyst injection pump, and the reaction was initiated. During the reaction, the molar ratio of ethylene and 1-hexene was maintained at the given molar ratio shown in Table 3 under controlled mass flow rate parameters. After 1 hour, the supply of ethylene and 1-hexene was stopped, and the reactor was cooled to 40°C. The reactor was then opened after venting. The polyethylene product was collected in a sample tray and dried at ambient temperature under atmospheric pressure.

[0080] The polymerization results are shown in Table 3 below. It can be seen that the catalyst productivity varies with the catalyst system and the ratio of 1-hexene to ethylene added to the reactor.

[0081] Table 3: Results of the polymerization experiment

[0082]

[0083] In this table, PE yield is expressed as the weight of polyethylene obtained in the experiment, in grams; productivity is defined as the weight of polyethylene obtained per unit weight of catalyst system, in g PE / g Cat. C6= / C2= indicates the 1-hexene / ethylene molar ratio.

[0084] The obtained product was characterized to obtain its density and molecular weight properties M. n M w and M z M n It is the number average molecular weight, M w It is the weight-average molecular weight, and M z These are Z-average molecular weights, expressed in kg / mol, and determined according to ASTM D6474 (2012). w / M n It is M w With M n The ratio, dimensionless, represents the molecular weight distribution. M z / M w It is M z With M w The ratio is also dimensionless. Density was determined according to ASTM D792 (2013) and expressed in g / cm³. 3 The results are shown in Table 4 below.

[0085] Table 4: Polymer Properties

[0086]

[0087] The molecular weight distribution of the polymers was determined by gel permeation chromatography (GPC) recorded at 150 °C on an Agilent PL-GPC 220 chromatograph equipped with a PL BV-400 viscometer and an infrared detector to collect signals for molecular weight analysis. The results are summarized in Table 4.

[0088] Comonomers are distributed in Figure 1-18The results are shown in Table 5. It can be seen that a reverse CCD distribution was observed for each experiment, and that it varied with the molar ratio of 1-hexene to ethylene added to the reactor. The GPC data were deconvolved using the method described in the literature (Niket Sharma and Yaliu, Ind. Eng. Chem. Res. 2019, 58, 14209-14226) to achieve the most probable fit for the two MW components. The results are summarized in Table 5. Clearly, the MW and partial weight percentage of each component varied with the molar ratio of 1-hexene to ethylene added to the reactor.

[0089] Table 5: Characteristics of the low molecular weight fraction and the high molecular weight fraction

[0090]

[0091] Crystallization-elution fractionation (CEF) analysis was performed on a Polymer Char CEF instrument. First, the sample was dissolved in 1,2,4-trichlorobenzene (TCB) at 1 mg / mL and maintained at 160 °C for 1 hour. The TCB was stabilized with 1000 ppm BHT. The polymer solution was injected into the system and pumped through the CEF column. The column was cooled to 35 °C at a flow rate of 0.05 mL / min and a cooling rate of 2 °C / min under continuous TCB flow. At the end of the cooling cycle, the temperature was held constant for 5 minutes. Finally, the sample was eluted through the TCB flow at a flow rate of 1 mL / min, while simultaneously heating the column to 160 °C at a rate of 4 °C / min. Results are as follows: Figure 19-21 As shown, the CEF distribution varies with the molar ratio of 1-hexene to ethylene added to the reactor.

[0092] Further polymerization experiments were conducted in which a reaction mixture containing ethylene and 1-hexene as a comonomer was polymerized in the presence of hydrogen.

[0093] A 1.6 L stainless steel reactor vessel equipped with a spiral stirrer and a heating / cooling control unit was heated to 110 °C for 2 hours at a nitrogen flow rate of 100 g / h. Afterward, the reactor was pressurized and purged with nitrogen, followed by ethylene purging. This purging cycle was repeated three times.

[0094] The reactor was then cooled to 88°C under ethylene pressurization to 10 bar. After venting, 4 ml of SC was added via a co-catalyst injection pump. Hydrogen was injected in the amounts specified in Table 6 under controlled flow rate parameters. Nitrogen was introduced to maintain a nitrogen pressure of 8 bar. Ethylene and 1-hexene with a 1-hexene / ethylene molar ratio of 0.12 were then introduced into the reactor under controlled flow rate parameters to maintain a pressure of 10 bar for both ethylene and 1-hexene in the reactor. After reaching stable temperature and pressure levels, 40 mg of the catalyst system was injected via a catalyst injection pump, and the reaction began. During the reaction, the ethylene and 1-hexene molar ratio was maintained at 0.12 under controlled flow rate parameters. After 1 hour, the supply of ethylene and 1-hexene was stopped, and the reactor was cooled to 40°C. The reactor was then opened after venting. The polyethylene product was collected in a sample tray and dried at ambient temperature under atmospheric pressure.

[0095] The polymerization results are summarized in Table 6. Clearly, the catalyst productivity varies with the hydrogen content added to the reactor. The molecular weight characteristics and density of the polymer are shown in Table 7. It can be observed that the molecular weight decreases with increasing hydrogen content. The comonomers are distributed in... Figure 22-24 As shown in the figure, a reverse CCD was implemented for each experiment. Table 8 lists the deconvolution results.

[0096] Table 6: Results of the polymerization experiment

[0097]

[0098] In this table, H2 is the amount of hydrogen supplied, in mg. H2 / C2 is the hydrogen / ethylene molar ratio.

[0099] Table 7: Polymer Properties

[0100]

[0101] Table 8: Characteristics of the low molecular weight fraction and the high molecular weight fraction

[0102]

Claims

1. A catalyst system comprising a first catalyst component A and a second catalyst component B. Component A is a component according to formula (I): And component B is a component according to formula (II): Where R1 and R2 are different and are preferably selected from and ; Each R12 is individually selected from H or an alkyl moiety containing 1-10 carbon atoms, preferably each R12 is individually selected from H, CH3 and phenyl moiety, more preferably each R12 is individually selected from H, CH3 and phenyl moiety and each R12 is the same; R3 is a structural moiety selected from ZrX2, HfX2 and TiX2, and X is selected from the group consisting of halogen, alkyl, aryl and aralkyl. R4-R11 are each hydrogen or a hydrocarbon structural moiety containing 1-20 carbon atoms, or R4 and R5, R5 and R6, R8 and R9 and / or R9 and R10 are fused to form a cyclic hydrocarbon structural moiety containing 4-20 carbon atoms, preferably the cyclic hydrocarbon structural moiety is a structural moiety containing a cyclohexene ring or a benzene ring, which may contain substituents containing 1-10 carbon atoms.

2. The catalyst system according to claim 1, wherein each R3 is selected from TiCl2, ZrCl2, HfCl2, Ti(CH3)2, Zr(CH3)2 and Hf(CH3)2, preferably selected from ZrCl2 and Zr(CH3)2.

3. The catalyst system according to any one of claims 1-2, wherein R1 and R2 are each selected from 1,2-phenylene: and 2,2'-biphenyl: .

4. The catalyst system according to any one of claims 1-3, wherein component A is according to formula (III): R4, R7, R8 and R11 are each individually selected as H, CH3, tert-butyl or phenyl; Preferably, R1 is 2,2'-biphenyl.

5. The catalyst system according to claim 4, wherein component A is [2,2'-bis(2-(4,5,6,7-tetrahydro)indenyl)biphenyl]-zirconium dichloride (IV).

6. The catalyst system according to any one of claims 1-5, wherein component B is according to formula (IV): R4, R5, R6, R7 and R8 are each individually selected as H, CH3, tert-butyl or phenyl, preferably R4, R5 and R6 are each CH3, and preferably R7 and / or R8 are phenyl; Preferably, R2 is 1,2-phenylene.

7. The catalyst system according to claim 6, wherein component B is 1,2-phenylene-[(2,4,7-trimethyl-1-indenyl)(1-phenyl-2-indenyl)]-zirconium dichloride (IV).

8. The catalyst system according to any one of claims 1-7, wherein the molar ratio of component A to component B is 0.1-4.

0.

9. The catalyst system according to any one of claims 1-8, wherein component A and component B are supported on a support, preferably wherein the two components are supported on the same support, preferably wherein the support is selected from silica, alumina, magnesium oxide, titanium dioxide, zirconium dioxide, clay, zeolite, graphite and polymer particles, preferably silica.

10. The catalyst system according to any one of claims 1-9, wherein the catalyst system comprises a co-catalyst, preferably wherein the co-catalyst is methylaluminoxane.

11. The catalyst system according to claim 10, wherein the catalyst system comprises ≥6.0 and ≤40.0 wt%, preferably ≥7.0 and ≤35.0 wt%, more preferably ≥10.0 and ≤30.0 wt% Al, relative to the total weight of the catalyst system.

12. The catalyst system according to any one of claims 1-11, wherein the catalyst system comprises ≥0.10 and ≤1.00 wt%, preferably ≥0.15 and ≤0.50 wt%, more preferably ≥0.15 and ≤0.30 wt% of the sum of Zr, Hf and Ti, relative to the total weight of the catalyst system.

13. A method for producing a catalyst system according to any one of claims 10-12, wherein the method comprises steps in the following order: (i) Treat the support with the co-catalyst, and then (ii) Add components A and B; or (i) Treat components A and B with the aforementioned co-catalyst, and then (ii) Add the carrier; or (i) Treating components A and B with the co-catalyst to obtain activated components A and B; (ii) Treat the support with the co-catalyst to obtain an activated support; and (iii) Combine the activated carrier with the activated components A and B.

14. A method for polymerizing a reaction mixture comprising ethylene and / or propylene using a catalyst system according to any one of claims 1-12.

15. The method of claim 14, wherein the method is an ethylene homopolymerization or copolymerization method.